2016
DOI: 10.1021/acs.bioconjchem.6b00468
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Transglutaminase-Mediated Conjugation of Interferon α-2b at Glutamine or Lysine Residues

Abstract: Interferon α (IFN α) subtypes are important protein drugs that have been used to treat infectious diseases and cancers. Here, we studied the reactivity of IFN α-2b to microbial transglutaminase (TGase) with the aim of obtaining a site-specific conjugation of this protein drug. Interestingly, TGase allowed the production of two monoderivatized isomers of IFN with high yields. Characterization by mass spectrometry of the two conjugates indicated that they are exclusively modified at the level of Gln101 if the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…Fontana et al. recently described MTG‐mediated lysine modifications of interferon α subtypes and avidin at multiple sites with the nonstoichiometric use of glutamine‐containing ZQG derivatives (ZQG, N ‐benzyloxycarbonyl‐ l ‐glutaminylglycine). As immobilization of enzymes can increase site selectivity, as, for example, reported for lipase, we speculated whether this would also apply to immobilized MTG.…”
Section: Methodsmentioning
confidence: 99%
“…Fontana et al. recently described MTG‐mediated lysine modifications of interferon α subtypes and avidin at multiple sites with the nonstoichiometric use of glutamine‐containing ZQG derivatives (ZQG, N ‐benzyloxycarbonyl‐ l ‐glutaminylglycine). As immobilization of enzymes can increase site selectivity, as, for example, reported for lipase, we speculated whether this would also apply to immobilized MTG.…”
Section: Methodsmentioning
confidence: 99%
“…Spolaore et al studied the reactivity of IFN α-2b to microbial mTGase to obtain a site-specific conjugation of this biopharmaceutical. Characterization by mass spectrometry of the conjugates indicated that among the 10 Lys and 12 Gln residues of the protein only Gln101 and Lys164 were selectively conjugated with a PEG-NH 2 for Gln101 and a PEG modified with carbobenzoxy--glutaminyl-glycine for Lys164 derivatization, with activity retention and improvements at pharmacokinetic levels (Spolaore et al, 2016). A mono-PEGylated derivative of filgrastim (granulocyte colonystimulating factor) was also prepared using mTGase.…”
Section: Microbial Transglutaminasesmentioning
confidence: 99%
“…The most well used partner for bioactive peptide drugs is human serum albumin. The choice of this protein has been justified for a variety of reasons [13,14] and its use is exemplified by human serum albumin-interferon fusion proteins [6,7,[15][16][17], which are typically expressed in yeast [15]. The expression of such proteins in E. coli is problematic since serum albumin contains 35 cysteine residues engaged in 17 disulphide bonds.…”
Section: Expression Of the Genes For The Chimeras 4 5 And 6 (Figure mentioning
confidence: 99%
“…In general, pegylation occurs randomly on the ε-amino group of surface lysine residues [4], though, site-specific pegylation has also been reported [5,6]. For more specific targeting, however, fusion technology to graft a protein specifically to the N-or C-terminal of a drug has been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation